Within-Couple Personality Concordance Over Time: The Importance of Personality Synchrony for Perceived Spousal Support. (15th September 2020) - Lewis, Nathan A; Yoneda, Tomiko
Abstract: Objectives: Within-couple similarities in personality traits tend to be positively associated with relationship well-being. However, research in this area is typically based on cross-sectional designs, thereby limiting examination of longitudinal personality concordance. Given that life experiences shape within-person change in personality, and that partners within a couple often experience similar life events, investigation of within-couple personality synchrony and associations with marital outcomes is warranted. Methods: Using data from 3, 988 couples (mean age at baseline = 67.0 years, SD = 9.6), multilevel dyadic growth models estimated within-couple similarity in baseline levels, change, and occasion-to-occasion variability for each of the Big Five personality traits over an 8-year follow-up. Bivariate growth models examined the effect of within-couple similarity on perceived spousal support, accounting for dependency within couples. Results: Adjusting for baseline age, education, functional ability, and relationship length, analyses revealed within-couple concordance between baseline levels of all 5 personality traits, as well as correlated within-couple fluctuations in neuroticism, extraversion, and openness over time. Similarity in openness, agreeableness, and neuroticism trajectories predicted spousal support. Couples were most similar in openness, showing correlated intercepts, change, and variability, and this longitudinal synchrony was particularly important for perceived spousal support in women. Discussion: These findings provide evidence for longitudinal personality synchrony over time within older adult couples. Further, concordance in neuroticism, extraversion, and openness predicted perceived spousal support, though there may be some gender differences in personality dynamics and relationship well-being. Effects of similarity were relatively small compared to actor and partner effects of these traits.